Effectiveness of Denture Cleansers for Removable Dentures: A Literature Review - Maqhfirah Amiruddin; Mohammad Dharma Utama; Chusnul Chotimah; Aditya Hari Asmara; Muh. Iqbal Shoaleh (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: The latest Indonesian Health Survey data indicate that 56.9% of the Indonesian population experiences dental and oral health issues, with 13.9% of individuals aged 15 years using complete dentures and 34.5% using partial dentures. An increased incidence of infection is associated with various predisposing factors, including denture use. Candida albicans is the primary etiological factor in denture stomatitis. This study aimed to evaluate the effectiveness of various types of denture cleansers. Review: This study employed a literature review approach by collecting and synthesizing relevant scientific research articles. A synthesis of 19 scientific research articles indicates that effervescent tablets are more effective for denture cleaning than cleansing pastes and herbal solutions, because of their practicality and high effectiveness in reducing biofilms, microorganisms, and fungi. Effervescent granules are effective against Streptococcus mutans and Candida albicans, although their efficacy depends on the concentration of the active ingredients and the temperature of the dissolving solution. The use of denture cleansing paste may increase the surface roughness of acrylic plates beyond the standard threshold of 0.2 µm. Herbal solutions are effective for cleaning dentures and inhibiting bacterial and fungal growth. Conclusion: Effervescent tablets are the preferred choice because of their high effectiveness in reducing biofilms, bacteria, and Candida albicans.